Proportion of nonsteroidal anti-inflammatory drug prescription in equine practice - Marco, Duz; John, Marshall; Tim, Parkin (Wiley, 2018)
BACKGROUND: There is little knowledge of the prescription of nonsteroidal anti-inflammatory drugs (NSAIDs) and whether their prescription varies between countries.